Dollarisation as an alternative exchange rate regime for emerging countries - Wessels, Buks (University of the Free State, 2006)
Over the past three decades exchange rate volatility has motivated a renewed search for stable and predictable exchange rate regimes. As a fixed exchange rate regime, dollarisation has increasingly been suggested as such an alternative, and is currently receiving renewed attention. This article is aimed at investigating the nature and rationale for such a regime, and also analysing its advantages and disadvantages. Furthermore, a critique of dollarisation, together with an analysis of its suitability for various circumstances and types of economies, is offered in order to determine its specific niche on the exchange rate spectrum. The regime is found to have merit, but to be applicable only to a limited number of countries with specific features.

Wisselkoersonbestendigheid gedurende die afgelope drie dekades het ’n hernieude soeke na wisselkoersstelsels met stabiliteit en voorspelbaarheid gemotiveer. Dollarisasie, as ’n vaste wisselkoersstelsel, word toenemend as sodanige alternatief voorgestel en geniet hernieude aandag. Hierdie artikel ondersoek die aard en rasionaal vir die stelsel, maar analiseer ook die voor- en nadele daarvan. Voorts word kritiek op dollarisering, gepaardgaande met ’n analise van die toepaslikheid daarvan vir uiteenlopende omstandighede en soorte ekonomieë, eweneens aangebied ten einde die spesifieke nis daarvoor op die wisselkoersspektrum te bepaal. Die bevinding is dat die stelsel gewis meriete het, hoewel dit slegs op ’n beperkte aantal lande met bepaalde eienskappe toepaslik is.
Keywords: Exchange rate; Dollarisation; Volatile capital flows; Emerging countries